In situ synthesis of noble metal nanoparticles on onion-like carbon with enhanced electrochemical and supercapacitor performance. Issue 8 (16th January 2017) - Wang, Changda; Wu, Chuanqiang; Chen, Shuangming; He, Qun; Liu, Daobin; Zheng, Xusheng; Haleem, Yasir A.; Song, Li
Abstract : Ultrafine noble metal nanoparticles decorated on onion-like carbon (OLC) were successfully prepared without any reductant or surfactant. Abstract : Ultrafine noble metal nanoparticles decorated on onion-like carbon (OLC) were successfully prepared without any reductant or surfactant. Particularly, the as-prepared Pt–OLC nanocomposite not only exhibited superior electrocatalytic activity and stability for the hydrogen evolution reaction as compared with the commercial 20% Pt/C, but also showed enhanced supercapacitor performance with a specific capacitance almost four times larger than that of OLC. Notably, the C–O functional groups on the surface of OLC will increase after the reaction because of the oxidation by O2 and chloroplatinic acid, which is very useful for the reuse of OLC and helpful for the decoration of noble metal nanoparticles on OLC. This work provides a simple and straightforward method for the facile preparation of metal composite nanocatalysts with high catalytic activity.